2016
DOI: 10.1111/ajad.12346
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled proof-of-concept trial of adjunctive topiramate for alcohol use disorders in bipolar disorder

Abstract: Background and Objectives Topiramate is effective for alcohol use disorders (AUDs) among non-psychiatric patients. We examined topiramate for treating comorbid AUDs in bipolar disorder (BD). Methods Twelve participants were randomized to topiramate or placebo for 12 weeks. Results The topiramate group, with two out of five participants (40%) completing treatment, experienced less improvement in drinking patterns than the placebo group, with five out of seven participants (71%) completing treatment. Discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“… 8 Unfortunately, treatment research for co-occurring BD and AD is remarkably limited. Only seven double-blind, placebo-controlled studies of medications for BD+AD have been conducted to date, 9 , 10 , 11 , 12 , 13 , 14 , 15 and only one of these studies demonstrated a medication (that is, valproate) effect on drinking. 12 Better understanding the mechanisms that give rise to co-occurring BD and AD could help to identify differences in genetic risk, prevention strategies and novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Unfortunately, treatment research for co-occurring BD and AD is remarkably limited. Only seven double-blind, placebo-controlled studies of medications for BD+AD have been conducted to date, 9 , 10 , 11 , 12 , 13 , 14 , 15 and only one of these studies demonstrated a medication (that is, valproate) effect on drinking. 12 Better understanding the mechanisms that give rise to co-occurring BD and AD could help to identify differences in genetic risk, prevention strategies and novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…A single study has investigated the effects of the anticonvulsant medication, Topiramate, on symptoms of bipolar disorder and co‐occurring alcohol dependence . Participants received either placebo or Topiramate (150 mg/d) in a 12‐week, randomized, proof of concept trial.…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment results are summarized in Supplemental Table 1. Ten studies were assessed as having a strong quality rating, 25,28,31,38,40,43,48,[53][54][55] 15 were assessed as having a moderate quality rating, 24,26,27,29,30,33,[35][36][37]44,46,49,50,52,56 and 7 were assessed as having a weak quality rating. 34,39,41,42,45,47,51 The Funnel plot (see Supplemental Figure 1) was asymmetrical suggesting that studies without statistically significant effects remain unpublished, particularly those with small participant sample sizes and those that investigated…”
Section: Quality and Bias Assessmentmentioning
confidence: 99%